Response of Medical Cannabis (Cannabis sativa L.) to Nitrogen Supply Under Long Photoperiod - Saloner, Avia; Bernstein, Nirit (Frontiers in Plant Science, 2020)
The development progression of medical cannabis plants includes a vegetative growth phase under long photoperiod, followed by a reproductive phase under short photoperiod. Establishment of plant architecture at the vegetative phase therefore affects its reproduction potential under short photoperiod. Nitrogen (N) is a main component of many metabolites that involve in central processes in plants, and is therefore a major factor governing plant development and structure. We lack information about the influence of N nutrition on medical cannabis functional-physiology and development, and plant N requirements are yet unknown. The present study therefore investigated the developmental, physiological and chemical responses of medical cannabis plants to N supply (30, 80, 160, 240 and 320 mgL-1 N) under long photoperiod. We report that the morpho-physiological function under long photoperiod in medical cannabis is optimal at 160 mgL-1 N supply, and significantly lower under 30 mgL-1 N, with visual deficiency symptoms, and 75% and 25% reduction in plant biomass and photosynthesis rate, respectively. Nitrogen use efficiency decreased with the increase in N supply, while osmotic potential, water use efficiency, photosynthetic pigments and total N and N-NO3 concentrations in plant tissues increased with N supply. The plant ionome was considerably affected by N supply. Concentrations of K, P, Ca, Mg, Na and Fe in the plant were highest under the optimal N level of 160 mgL-1 N, with differences between organs in the extent of accumulation. The majority of the nutrients tested, including P, S, Zn, Mn, Fe and Cu tented to accumulate in the roots >leaves>stem, while K and Na tented to accumulate in the stem>leaves> roots, and total N, Ca and Mg accumulated in leaves>roots>stem. Taken together, the results demonstrate that the optimal N level for plant development and function at the vegetative growth phase is 160 mgL-1 N. Growth retardation under lower N supply (30-80 mgL-1) results from restricted availability of photosynthetic pigments, carbon fixation and impaired water relations. Excess uptake of N under supply higher than 160 mgL-1 N, promoted as well physiological and developmental restrictions, by ion-specific toxicity or an indirect induced restriction of carbon fixation and energy availability.